2000
DOI: 10.1039/b005028h
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric synthesis of febrifugine and isofebrifugine using yeast reduction

Abstract: The antimalarial agents febrifugine ((+)-1) and isofebrifugine ((+)-2) were asymmetrically synthesized from chiral piperidin-3-ol ((+)-4), which was prepared by the reductive dynamic optical resolution of the 3-piperidone derivatives ((±)-3) using baker's yeast.Febrifugine ((+)-1) is an antimalarial agent that was isolated from Dichroa febrifuga and Hydrangea umbellata along with isofebrifugine ((+)-2). 1a-c The plane structure 2a of (+)-1 and (+)-2 was first proposed in 1950. Subsequently, the relative 2b and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…17,18) Piperidin-3-one derivatives are used as precursors for the synthesis of antimalarial agents febrifugine and isofebrifugine. 19) Earlier reports have indicated that biological activity is significant in piperidone systems possessing aromatic substitutions in the 2-and/or 6-positions.…”
Section: )mentioning
confidence: 99%
“…17,18) Piperidin-3-one derivatives are used as precursors for the synthesis of antimalarial agents febrifugine and isofebrifugine. 19) Earlier reports have indicated that biological activity is significant in piperidone systems possessing aromatic substitutions in the 2-and/or 6-positions.…”
Section: )mentioning
confidence: 99%
“…1 Recently, we have demonstrated that (S)-3-hydroxyglutarimide could serve as a useful building block for the asymmetric synthesis of bioactive piperidines such as (+)-febrifugine, (+)-isofebrifugine, 2 (+)-L-733,060, and (+)-CP-99,994. 3,4 In the early phase of these studies, it was observed that the optical rotation of benzyl [ 5 and +78.5 (c = 1.0, EtOH) 6 }. This implied that racemization took place in the synthetic route, probably during the base-promoted ring-expansion reaction leading to 3-hydroxyglutarimide.…”
mentioning
confidence: 99%
“…Among the nitrogen containing six-member heterocylic compounds, the pyridine or piperidine structural is often found in naturally occurring bioactive compounds such as alkaloids 2 . Piperidinone derivatives are used as precursors for the synthesis of anti-malarial, febrifugine, and isofebrifugine 3 . Piperidinones display varied and potent biological properties like antiviral, antitumour, analgesic, local anaesthetic, antimicrobial, fungicidal, herbicidal, insecticidal, antihistaminic, antiinflammatory, anticancer, CNS stimulant, and depressant properties [4][5][6] .…”
Section: Introductionmentioning
confidence: 99%